Intensifying Chitin Hydrolysis by Adjunct Treatments – an Overview - Junqueira-Conceicao Goncalve, M (John Wiley and Sons Ltd, 2017)
Chitin is, after cellulose, the most abundant organic natural polysaccharide on Earth, being synthesized as a dominant component in the exoskeletons of crustaceans, among other sources. In the processing of seafood for human consumption, between 40 and 50% of the total raw material mass is wasted, causing a significant problem for the environment owing to its slow degradation. Efforts to find uses for chitin derivatives, particularly their oligomers, have intensified since these chemicals are highly functional and offer a wide range of applications, especially as antimicrobial agent. As a consequence, some adjunct treatments, either chemical or physical in nature, have been employed to assist acid and enzymatic hydrolysis. This work provides a detailed review of the methods employed to intensify the formation of chitin oligomers, particularly focusing on the adjunct treatments used (microwave, ultrasonication, steam explosion and gamma irradiation), and an evaluation of the yield and characteristics of the oligomers formed. Adjunct treatments are more suitable for enzymatic hydrolysis since these treatments modify the chitin structure, and enhance the hydrolysis rate and yield of the oligomers, under milder reaction conditions. For future research, it would be worth trying pre-treatments like the application of high-pressure to chitin in order to lower its crystallinity. © 2017 Society of Chemical Industry. © 2017 Society of Chemical Industry